STUDY ON DIVERSITY OF AQUATIC INSECTS IN RAMAUA RESERVOIR OF GWALIOR DISTRICT (M. P.) - Sharma, K.; Lodhi, R. K.; Rao, R. J. (International Journal of Research -GRANTHAALAYAH, 2020)
Aquatic insects are those which live a part of their life cycle in water. In addition to their significant ecosystem function aquatic insects are also a primary source of food for fishes and amphibians. Inland wetlands of India serve as the habitat for more than 500 species of aquatic insects which are mainly from Ephimeroptera, Odonta and Trichoptera. The study was conducted during early hours of the day from August, 2019 to November 2019. Three sites were selected for the study i.e. vegetation site, agricultural site and disturbed vegetation site. The checklist of recorded aquatic insects is shown with their taxa, order, family and scientific name and common name. Total 24 species of aquatic insects were found in three different sites. The study of population of insects in different sites revealed the fact that the population of aquatic insects was governed by abiotic and biotic factors.